Charnia at 50: Developmental models for Ediacaran fronds - Antcliffe, J; Brasier, M (2008)
Correct interpretation of the Ediacara biota is critical to our understanding of the dramatic events at the base of the Cambrian. We review here the history of thought and examine new laser images of the holotype of Charnia masoni Ford, 1958, of the Ediacara biota, in terms of growth and development. Growth and development are argued to provide critical tools for understanding this and other enigmatic fossil groups. We show that Charnia cannot be related to the modern cnidarian group, the sea pens, with which it has for so long been compared, because they have opposite growth polarities. This is shown by our work on material collected by HMS challenger. Recent evolutionary studies also show that sea pens are a highly derived group of actively burrowing cnidarians that are likely to have evolved later than the Palaeozoic. The traditional paradigm of translating Phanerozoic animal phyla back into the Ediacaran is therefore questioned. © 2008 The Palaeontological Association.